Head injury from falls in children younger than 6 years of age. Issue 11 (21st August 2015) - Burrows, P; Trefan, L; Houston, R; Hughes, J; Pearson, G; Edwards, R J; Hyde, P; Maconochie, I; Parslow, R C; Kemp, A M
Abstract : The risk of serious head injury (HI) from a fall in a young child is ill defined. The relationship between the object fallen from and prevalence of intracranial injury (ICI) or skull fracture is described. Method: Cross-sectional study of HIs from falls in children (<6 years) admitted to UK hospitals, analysed according to the object fallen from and associated Glasgow Coma Score (GCS) or alert, voice, pain, unresponsive (AVPU) and CT scan results. Results: Of 1775 cases ascertained (median age 18 months, 54.7% boys), 87% (1552) had a GCS=15/AVPU=alert. 19.3% (342) had a CT scan: 32% (110/342) were abnormal; equivalent to 5.9% of the overall population, 16.9% (58) had isolated skull fractures and 13.7% (47) had ICI (49% (23/47) had an associated skull fracture). The prevalence of ICI increased with neurological compromise; however, 12% of children with a GCS=15/AVPU=alert had ICI. When compared to falls from standing, falls from a person's arms (233 children (mean age 1 year)) had a significant relative OR for a skull fracture/ICI of 6.94 (95% CI 3.54 to 13.6), falls from a building (eg, window or attic) (mean age 3 years) OR 6.84 (95% CI 2.65 to 17.6) and from an infant or child product (mean age 21 months) OR 2.75 (95% CI 1.36 to 5.65). Conclusions: Most HIs from a fall in these children admitted to hospital were minor. Infants, dropped from a carer's arms, those who fell from infant products, a window, wall or from an attic had the greatest chance of ICI or skull fracture. These data inform prevention and the assessment of the likelihood of serious injury when the object fallen from is known.